2013
DOI: 10.12659/msm.889880
|View full text |Cite
|
Sign up to set email alerts
|

Activity of sputum p38 MAPK is correlated with airway inflammation and reduced FEV1 in COPD patients

Abstract: BackgroundInflammation and remodeling of the small airways are major determinants of the progression and severity of COPD. The present study explored the correlation between sputum p38 mitogen-activated protein kinase (MAPK) activity and airway inflammation and reduction of lung function in the patients with chronic obstructive pulmonary disease (COPD).Material/MethodsSputum samples were collected from 48 COPD patients and 12 healthy persons. Sputum p38 MAPK activity was measured by Western blotting and sputum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 42 publications
(60 reference statements)
0
8
1
Order By: Relevance
“…In our study, both sUA levels and sUA/creatinine ratios were significantly higher in COPD patients than in healthy controls. It has been suggested that sUA levels increase in the presence of persistent systemic inflammation caused by COPD [23]. Interestingly, sUA levels and sUA/creatinine ratios were not associated with the severity of COPD in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…In our study, both sUA levels and sUA/creatinine ratios were significantly higher in COPD patients than in healthy controls. It has been suggested that sUA levels increase in the presence of persistent systemic inflammation caused by COPD [23]. Interestingly, sUA levels and sUA/creatinine ratios were not associated with the severity of COPD in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…8 In this regard, it is noteworthy that high sputum levels of phospho-p38 MAPK can be detected in COPD patients. 42 Furthermore, such an enhanced activity of p38 MAPK was closely associated with several biological and lung functional parameters, including high concentrations of sputum neutrophils and IL-8, as well as low values of forced expiratory volume in one second (FEV 1 ). 42 Taken together, the above findings suggest that in COPD p38 MAPK activation is markedly correlated with both pulmonary inflammation and the progressive deterioration of respiratory function.…”
Section: Role Of P38 Mapk In Copd Pathophysiologymentioning
confidence: 98%
“… 243 Each subtype of p38MAPK has unique functions due to differential expression across tissue types and different regulatory kinases and downstream genes, hence their targeting comes with adverse effects. Although some clinical trials are in progress, due to severe side effects such as those caused by an undesired pharmacological activity, suppression of the innate immune response to viral and bacterial infections, and damage to the central nervous system and liver, 244 , 245 these drugs remain challenging for a clinical application. There is a need to develop inhaled formulations and selective inhibitors of the α-δ subgroups.…”
Section: New Molecular Targeted Drugsmentioning
confidence: 99%